Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/ijfs.14200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of baked wheat germ on gluten protein network in steamed bread dough

Abstract: Summary The effect of baked wheat germ (BWG) on the gluten network structure in steam bread dough was investigated. The secondary structure, free sulphydryl (‐SH) content, disulphide (‐SS‐) bonds content and microstructure of gluten were analysed to evaluate gluten structural changes. The addition of different amounts of BWG (0, 2, 4, 6, 8, 10, and 12%) in dough resulted in decreased content of α‐helix and β‐sheet structures, but increased random coils, which indicated that a disordered structure was formed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…As can be seen in Figure S1, the native flour steamed bread had tighter internal structure than model steamed bread, whereas the native flour steamed bread had lower whiteness than model steamed bread. This may be due to the fact that water‐soluble proteins reduced the whiteness of the native flour (Zhan et al, 2019). It was also found that the gas hole of C dough steamed bread was more obvious than that of R dough steamed.…”
Section: Resultsmentioning
confidence: 99%
“…As can be seen in Figure S1, the native flour steamed bread had tighter internal structure than model steamed bread, whereas the native flour steamed bread had lower whiteness than model steamed bread. This may be due to the fact that water‐soluble proteins reduced the whiteness of the native flour (Zhan et al, 2019). It was also found that the gas hole of C dough steamed bread was more obvious than that of R dough steamed.…”
Section: Resultsmentioning
confidence: 99%
“…(2007) also observed an increase in water absorption when replacing flour by milled WG, during farinograph tests. This consequence was associated to WG proteins capacity to absorb water, but other molecules like fibre and starch could have a concomitant effect (Zhan et al ., 2019). Ling et al .…”
Section: Resultsmentioning
confidence: 99%
“…Some mechanisms were suggested to justify this: gluten dilution due to the replacement of flour by SWG, water competition between flour and WG components, and physically disruption of gluten and starch network by germ particles. These results are in agreement with other authors, which observed a less structured gluten at microscopic level when thermally treated (Zhan et al ., 2019) or milled WG (Sun et al ., 2015) was added to dough. Evidence of water competition and dilution of gluten in dough containing wheat germ were also reported before in bibliography (Gómez et al ., 2012; Sun et al ., 2015; Boukid et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…the presence of BWG stimulated the loosening of the gluten network structure and the separation between starch granules and the gluten network (Zhan et al, 2019).…”
Section: Fermentation Properties Of Doughmentioning
confidence: 96%
“…The probably reason was that BWG dough group is similar to the fibrous structure formed by hydrated gluten and wheat germ protein, showed less flexibility and harder. Adding 10% BWG might result in larger-size and relatively uniform of gas cell, but the structure was unstable, easy to be destroyed with the further increase of BWG (Zhan et al, 2019). Therefore, when the amount of BWG is controlled within 4%, the dough has a relatively favorable fermentation height and gas retention capacity.…”
Section: Fermentation Properties Of Doughmentioning
confidence: 99%